Unconventional monetary policy and corporate bond issuance - Roberto A. De Santis; Andrea Zaghini (European Central Bank (ECB), 2019)
We assess the effect and the timing of the corporate arm of the ECB quantitative easing (CSPP) on corporate bond issuance. Because of several contemporaneous measures, to isolate the programme effects we rely on one key eligibility feature: the euro denomination of newly issued bonds. We find that the significant increase in bonds issuance by eligible firms is due to the CSPP and that this effect took at least six months to unfold. This result holds even when comparing firms with similar ratings, thus providing evidence that unconventional monetary policy can foster a financing diversification regardless of firms' risk profile.
Keywords: E52; G15; G32; 330; Quantitative easing; CSPP; corporate bond market